Memory effects in polymer brushes showing co-nonsolvency effects - Schubotz, Simon; Honnigfort, Christian; Nazari, Saghar; Fery, Andreas; Sommer, Jens-Uwe; Uhlmann, Petra; Braunschweig, Bjoern; Auernhammer, Guenter K. (Advances in Colloid and Interface Science, 2021)
Densely packed polymer chains grafted to a substrate, especially polymer brushes, have been studied intensively. Of special interest are systems that react to changes in external conditions or”remember” previous conditions. With this focus, we explore the properties of PNiPAAm brushes and relate published work to own results. The co-nonsolvency effect leads to a collapse of a PNiPAAm brush for a certain mixing ratio of ethanol in water. This also influences the wetting behavior of PNiPAAm brushes. We show that through prewetting of a brush with different liquids (water and ethanol), the contact angle of subsequent water drops changes significantly. To explain this change, the swelling of the brush was investigated with spectroscopic ellipsometry and the orientation of the molecules at the surface with sum-frequency generation (SFG). Only little change in swelling was found. The SFG measurements reveal in the ethanol prewetted case a well ordered hydrophobic methyl layer at the interface, which is consistent with the contact angle measurement.
CRIS-Team Scopus Importer:2022-04-14